An integrated approach to the safety assessment of food additives in early life. (2nd June 2017) - Constable, Anne; Mahadevan, Brinda; Pressman, Peter; Garthoff, Jossie A; Meunier, Leo; Schrenk, Dieter; Speijers, Gerrit; O'Sullivan, Aaron; Hayes, A Wallace
During the development of international standards by the Codex Alimentarius Commission, infant foods and their constituent ingredients are subject to rigorous risk analysis and are strictly regulated by many authorities. Various jurisdictions have approved only a limited number of additives specifically with regard to infant foods to fulfill specific technical requirements of quality. As part of the approval process, a rigorous safety assessment is essential to confirm that the use of additives does not pose any health risk for the consumer. An acceptable daily intake (ADI) may be derived from the toxicological databases. However, the ADI may not be applicable to infants because of the possible developmental sensitivities and potentially high exposure scenarios, leading to possible lower margins of safety than would often be determined for adult populations. There is interest in defining better food safety assessment approaches for pre-weaned infants aged less than 12–16 weeks. To confirm safe use in infants, we reviewed the suitability of the existing safety databases of six additives with historical uses in infant nutrition products. To determine further toxicity testing strategies, it is necessary to understand whether the chemical used in the additives is identical to endogenous physiological metabolites and/or whether immature organs of infants are targets of toxicity. Combined with an in-depth review of the existing relevant toxicological and nutritional studies, this integrated approach will facilitate decision-making. We propose a decision tree as a tool within this approach to help guide appropriate data requirements and identify data gaps. In cases of reasonable uncertainty, studies of targeted juvenile should be considered to investigate the safe use levels in food products.